Road Vehicle Automation - Meyer, Gereon; Beiker, Sven (Lecture Notes in Mobility,, 2014)
This contributed volume covers all relevant aspects of road vehicle automation including societal impacts, legal matters, and technology innovation from the perspectives of a multitude of public and private actors. It is based on an expert workshop organized by the Transportation Research Board at Stanford University in July 2013. The target audience primarily comprises academic researchers, but the book may also be of interest to practitioners and professionals. Higher levels of road vehicle automation are considered beneficial for road safety, energy efficiency, productivity, convenience, and social inclusion. The necessary key technologies in the fields of object-recognition systems, data processing, and infrastructure communication have been consistently developed over the recent years and are mostly available on the market today. However, there is still a need for substantial research and development, e.g. with interactive maps, data processing, functional safety, and the fusion of different data sources. Driven by stakeholders in the IT industry, intensive efforts to accelerate the introduction of road vehicle automation are currently underway.